Dinamika Konstitusionalitas Undang-Undang Cipta Kerja Pasca Putusan Mahkamah Konstitusi Nomor 91/PUU-XVIII/2020 dan 54/PUU-XXI/2023 - Arrafi Bima Guswara; Ali Imran Nasution (Jurnal USM Law Review)
This research aims to examine the repairing Law no 11 of 2020 concerning Job Creation by issuance of Perppu No. 2 of 2022 concerning Job Creation and Questioning the constitutionality of Law no. 6 of 2023 after Constitutional Court Decision no. 54/2023. Constitutional Court Decision No. 91/2020 decides Law no. 11 of 2020 concerning Job Creation as Conditionally Unconstitutional and mandates law makers to improve it with meaningful community participation. The government took action to the decision by issuing Perppu no. 2 of 2022 concerning Job Creation. Constitutional Court Decision No. 54/2023 states the issuance of Perppu no. 2 of 2022 concerning Job Creation fits on UUD NRI 1945. Even though the Constitutional Court's decision is final and binding, it is considered to harm substantive justice in society. The research method applied is normative juridical research with a statutory approach and a case approach supported by primary and secondary legal materials which are then managed qualitatively. Previous research analyzed the constitutionality of the job copyright law based on Constitutional Court Decision no. 91/PUU-XVIII/2020, but this research analyzes the dynamics of the constitutionality of the job copyright law based on Constitutional Court Decision No. 91/PUU-XVIII/2020 and 54/PUU-XXI/2023. The results obtained from this research are, the issuance of Perppu no. 2 of 2022 concerning Job Creation which was subsequently enacted into Law no. 6 of 2023, againts Counstitutional Court Decision No. 91/2020, had requirement to provide meaningful participation, and was enacted into law when it no longer had any operational power.